(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2024)
The Graduate Assessment Form restructuring in the teaching area presented changes resulting from the expansion of qualitative indicators in the general assessment process of graduate programs (GPs). Peer review is the modality established by CAPES for assessing programs, with training reflection as a guideline, which contributes to the feedback needed to improve teaching processes and procedures. In the committees, consultants work together to develop and/or detail the criteria to support the organization of work and the design of assessment strategies. Since the 2017–2020 Quadrennial Assessment, concerns have arisen about what GPs, in the professional modality of the teaching area, have prioritized to value the quality of information included in the CAPES Data Collection report. In this context, this article, in essay format, adopts a theoretical-descriptive nature to reflect on the meaning of each part of the Assessment Form, and aims to contribute to assessment inherent to the reality of programs and their training and research practices, valuing their insertion, modality and vocation, in line with the teaching area criteria. Based on the authors’ experience in the assessment process developed in the last four years, the adopted criteria that guide assessment work are discussed, with contributions to improving the programs.